Cultural Entanglements in the Urban Fabric: A case of festivals in Old Dhaka and its impacts - Khandoker Upama Kabir; Mohammad Fuhad Anwar Sinha (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
The historic city center of Dhaka, Bangladesh also known as ‘Puran Dhaka’, holds a lot of history and heritage of the region. This historic site has constantly been neglected and urban development has been done without integrating this part of the city into the plans. As a result, the traditional festivals that take place here annually create a greater impact on the urban fabric of the whole city. This paper will attempt to look at the importance of these traditions, how these festivals influence the urban life of the community and identity, and whether or not it has any significant effect on the economy. Through the use of both primary (interviews with the residents) and secondary sources and SWOT analysis, this paper will attempt to identify the issues faced during these festivals. This paper will also try to suggest some basic remedies based on general comparisons between case studies of similar festivals celebrated globally.